Erudizione e cultura storica nella Sicilia del XIX secolo: Il carteggio tra Michele Amari e Raffaele Starrabba (1866-1900) : Erudition and Historical Culture in Nineteenth-Century Sicily: The Correspondence between Michele Amari and Raffaele Starrabba - Serena Falletta (FedOA - Federico II University Press, 2018)
Through the correspondence between Michele Amari (1806-1889) and Raffaele Starrabba (1834-1906), the volume provides a glimpse of the historiographical panorama of the Italian nineteenth century in the crucial period that followed the birth of the Nation. The correspondence also illuminates the figure of Baron Starrabba, who played a fundamental role in the local archival administration and was the founder, with Isidoro Carini, of the Sicilian Society for the History and of its periodical, the "Archivio Storico Siciliano".
Italian
Keywords: Raffaele Starrabba; Letters; Arabistic; Michele Amari; History; Medieval History; Palermo; Sicily; Erudition; Historiography; Nineteenth Century; Archives; Archivistic; Correspondance